Do KATP channels have a role in immunity? - Feske, Stefan; Colucci, Francesco; Coetzee, William A. (Frontiers in Immunology, 2024)
Ion channels, exchangers and pumps are expressed ubiquitously in cells from all phyla of life. In mammals, their role is best described in excitable cells, where they regulate the initiation and propagation of action potentials. There are over 70 different types of K+ channels subunits that contribute to these processes. In non-excitable cells, K+ channels set the resting membrane potential, which in turn drives the activity of other translocators. K+ channels also help maintain cell volume, influence cell proliferation and apoptosis and regulate Ca2+ signaling, which in turn is crucial for many cellular processes, including metabolism, secretion, and gene expression. K+ channels play crucial roles in the activation, proliferation and a variety of other functions in cells of the innate and adaptive immune system. The ATP-sensitive K+ (KATP) channel has an established role in diverse cells, but its presence and function in immunity is scantly described. Public gene expression databases show that KATP channel subunits are highly expressed in NKT and NK cells, and that they are significantly upregulated after infection in CD8+ T cells and macrophages. We discuss these findings in the light of the available literature and propose a role for KATP channels in cytotoxicity of cells that are primed for a rapid immune response. Possible underlying molecular mechanisms are discussed.